Respuesta de la comunidad frente a la violencia doméstica contra la mujer - Oblitas Bejar, Beatriz (2007)
This artic!e portravs thefindings o( a rescarch carried out in a Lima Metropolitana urban commuuitv and ina rural community ofthe highlunds (!{Arequipa. 11shows thatfirmlv established cultural ClIst01l/S 111minto aframework within which violence within the [amily against wontan is perceived as a natural ph(,)/()/IICI/OII. Thus. organizations (//1(/ persous restrain themselves from doing anvthing about it. As emeofthe social orgauizations leader pointed out. h'OI/lt'11 wlio sltjJí.'reti uggression didn t wish al/y intervention to take place since ir was «a master O¡¡{¡, panaining the couple». Therc are no ejfir'acio({s strcucuie» [or thc (/'''/1'1'1'('11("(' 01' domestic violence against 11'011/('1/, neithcr 0/1 {lit individua! (J,. a collcctive /('1"('/, uorfront grass-roots local organizations orfroni IIIt! gOI'Crl/III!!II/.